Efforts to Improve Thematic Learning Achievement Material Theme 5 my Experience Sub Theme 2 My Experience with Friends by Applying the Learning by Doing Learning Model to Students of Grade I MI Negeri 3 Jakarta Academic Year 2021/2022 - Nurhayati Nurhayati (Journal of Social Research, 2023)
This research is based on the following problems: (a) Does learning by doing affect Thematic learning achievement in Grade I Students? (b) How high is the level of mastery of Thematic subject matter with the application of learning by doing learning methods to Grade I Students? The objectives of this study are: (a) To uncover the flow of learning by doing on Thematic learning achievement in Grade I Students. (b) Want to know how far the understanding and mastery of Thematic subjects after the application of learning by doing learning to Grade I Students. This study used three rounds of action research. Each round consists of four stages, namely: design, activity and observation, reflection, and refisi. The target of this study was Grade I students . The data obtained are in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysts, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (64%), cycle II (75%), cycle III (100%). The conclusion of this research is that the learning by doing method can have a positive effect on the learning motivation of Grade I students, and this learning model can be used as a thematic alternative